Imaging the term neonatal brain. Issue 5 (18th July 2018) - Sorokan, S Todd; Jefferies, Ann L; Miller, Steven P
Abstract: Brain imaging is important for the diagnosis and management of sick term neonates. Although ultrasound and computed tomography may provide some information, magnetic resonance imaging is now the brain imaging modality of choice because it is the most sensitive technique for detecting and quantifying brain abnormalities and does not expose infants to radiation. This statement describes the principles, roles and limitations of these three imaging modalities and makes recommendations for appropriate use in term neonates. The primary focus is the brain of term infants with neonatal encephalopathy, many of whom are diagnosed with hypoxic-ischemic encephalopathy.